2014
DOI: 10.1002/btpr.1948
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to monitor clearance of host cell proteins associated with monoclonal antibodies

Abstract: Co-purification of a subset of host cell proteins (HCPs) with monoclonal antibodies (mAbs) during the capture of mAbs on Protein A affinity chromatography is primarily caused by interactions of HCPs with the mAbs. To date, there is limited information about the identity of those HCPs due to the difficulty in detecting low abundance HCPs in the presence of a large amount of the mAb. Here, an approach is presented that allows identification of HCPs that specifically associate with the mAb, while avoiding interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 30 publications
3
128
0
Order By: Relevance
“…Which proteins are likely to adsorb can be assessed to a first approximation from electrostatic considerations; for instance, 46% of the identified host cell proteins identified in mAb production from Chinese hamster ovary cells have isoelectric points below 7.3 (Aboulaich et al, 2014), so they would be expected to bind at pH values typical for cell culture. These complement the current body of work on depth filtration in bioprocessing and extend our understanding of a depth filter as a composite unit.…”
Section: Discussionmentioning
confidence: 99%
“…Which proteins are likely to adsorb can be assessed to a first approximation from electrostatic considerations; for instance, 46% of the identified host cell proteins identified in mAb production from Chinese hamster ovary cells have isoelectric points below 7.3 (Aboulaich et al, 2014), so they would be expected to bind at pH values typical for cell culture. These complement the current body of work on depth filtration in bioprocessing and extend our understanding of a depth filter as a composite unit.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the third step based solely on ionic interactions, their amount fell to acceptable levels. It has been previously shown that some HCPs can directly interact with mAbs [38,39]. Such is the case for glutathione S-transferase P1, complement C1r-A subcomponent, peroxiredoxin-1, lipoprotein lipase and procollagen C-endopeptidase enhancer 1.…”
Section: Tablementioning
confidence: 96%
“…Specifically, one of the difficult-to-remove HCPs noted above, lipoprotein lipase (LPL), which was also identified in other studies of HCP persistence (Aboulaich et al, 2014; Doneanu et al, 2012), hydrolyzes ester bonds within triglycerides to form alcohol and fatty acid molecules (Nilsson-Ehle et al, 1980). Given the structural similarities between polysorbates and triglycerides, it is hypothesized that LPL may enzymatically degrade polysorbates and consequently negatively impact mAb stability.…”
Section: Introductionmentioning
confidence: 97%